Nila Pratiwi Perancangan Sistem Rumah Cerdas Berbasis Internet of Things (IoT) Menggunakan Aplikasi BLYNK - Nila Pratiwi (Pusat Riset dan Inovasi Nasional, 2023)
Increased use of the internet has resulted in innovation in control systems. The Internet of things (IOT) is an innovation where some electronic devices can be controlled remotely by utilizing the internet to obtain a more efficient control system, and save time. So a tool based on the Internet of things (IOT) is made that uses a smartphone as a controller for household appliances such as lights and fans. Where this tool uses the Arduino Uno as the brain to do the work and the WIFI module ESP-01 as a connection for the wifi signal which is connected to a smartphone that has been programmed via Arduino software, while several trials of the Internet Of Things (IOT) tool were carried out, namely distance trials to be tested from the closest distance of 1 meter and the farthest 100 meters to control household appliances.